Development of reverse transcription loop-mediated isothermal amplification for rapid detection of Sars-Cov-2 - Attah, Obande Godwin (2022)
COVID-19 began in Wuhan, China as a disease of unknown origin, presenting with typical pneumonia in late 2019. Within a short time, the disease spread to almost every part of the world with over 238 million infections and over 4.8 million mortalities as of 12th October 2021. RT-PCR is the gold standard test for confirming the disease, but issues relating to its tedious workflow, lengthy time-to-result, expensive equipment need, and high skill requirements limit its use especially in resource-limited countries. Rapid antigen and antibody test kits are faster and cheaper, but less sensitive, and cross-reactivity with related viruses have been reported. This work aimed at developing a suitable alternative assay for detecting SARS-CoV-2 using reverse transcription loop-mediated isothermal amplification (RT-LAMP). LAMP primer sets targeting the nucleocapsid (N) gene of SARS-CoV-2, and the human RNase P (RNAP) gene (internal amplification control, IAC) were designed using PrimerExplorer V5. Primers were screened for specificity and efficiency using synthetic N and RNAP genes by PCR and conventional LAMP reactions. The final choice of N gene primer was based on amplification speed, specificity for SARS-CoV- 2 and absence of background amplification in negative control. Concentrations of primers (outer, inner and loop), magnesium sulfate (MgSO4), betaine, dNTPs, Bst 2.0 DNA polymerase enzyme, reverse transcriptase enzyme as well as incubation temperature were optimized. Final RT-LAMP assay was optimized using in vitro transcribed RNA from N gene of SARS-CoV-2. Amplification products were detected visually with addition of hydroxynaphthol blue (HNB) dye, and an assembled lateral flow strip (LFS) that simultaneously detected SARS-CoV-2 N gene and RNAP IAC. Both methods detected up to 1 copy of IVT RNA within 40 minutes at 65oC. Diagnostic performance was tested using 162 clinical samples (81 positive and 81 negative) confirmed with RT-PCR. Sensitivity and specificity were 97.53 % (95 % CI: 91.36 - 99.70 %) for the colorimetric RT-LAMP assay, while LFS detection was 97.53 % (95 % CI: 91.36 - 99.70 %) sensitive and 90.12 % (95 % CI: 81.46 - 95.64 %) specific. HNB-RT-LAMP and LFS-RT-LAMP were 97.53 % and 93.83 % accurate, respectively. Overall, 97.5 % of RT-PCR confirmed clinical samples having Ct value 12.87 – 41.10 were detected by both assays. Based on in silico analysis, the RT-LAMP primers could also detect Alpha, Beta, Delta, Gamma, Lambda and Mu SARS-CoV-2 variants from within and outside Malaysia. Although further work on the RT-LAMP assay is required, the assay can be used to augment RT-PCR in community surveillance testing especially in resource-limited settings as the COVID-19 pandemic continues.